Hackerspaces as technofeminist sites for experiential learning. Issue 1 (2nd January 2022) - Richterich, Annika
ABSTRACT: Hackerspaces are physical community spaces where technology enthusiasts meet. Despite the term 'hacking' being widely associated with cybercrime, hackerspaces are not only perfectly legal but resourceful, skilled communities: members cultivate digital expertise and technological craftsmanship in experiential learning practices. While the educational value of hackerspaces has been rightfully acknowledged, not everyone equally benefits from potential learning opportunities. Many hackerspaces struggle with issues related to communal homogeneity, being frequently dominated by white, male members. Underrepresented groups, notably women, non-binary, genderqueer, and transgender members, have experienced discrimination and harassment. In response, explicitly feminist hackerspaces emerged. How are learning approaches and involved technology different in such feminist hacking communities? More specifically, how do feminist hackerspaces choose, discuss, and shape technology in their learning practices and educational approaches? Methodologically drawing on a single case study approach, the paper argues that hackerspaces have the potential to act as intersectional, technofeminist sites for experiential learning.